The Relationship between Merdeka Mengajar Platform Utilisation and Learning Management Effectiveness - Jon Hendri; Hendrizal Hendrizal; Adriantoni Adriantoni (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study was motivated by various obstacles public elementary school teachers in Padang Selatan District face in utilising the Merdeka Mengajar Platform (PMM) and in managing learning based on the Merdeka Curriculum. The research aims to describe the level of PMM utilisation, examine the effectiveness of learning management, and analyse the relationship between the two variables. A quantitative approach with a descriptive survey method was employed. The sample consisted of 78 teachers selected through stratified proportional random sampling from a population of 157 teachers. Data were collected using a Likert-scale questionnaire and analysed through simple linear regression. The findings reveal that PMM utilisation was categorised as good (86.39%), while learning management effectiveness was 88.09%. The analysis indicates a significant relationship between PMM utilisation and learning management effectiveness, with a contribution of 74.4%. These results demonstrate that PMM plays a substantial role in supporting the implementation of the Merdeka Curriculum. Practically, optimising PMM usage enhances learning management effectiveness, while theoretically, it reinforces the importance of integrating educational technology to improve teachers' professional performance and instructional management quality.